Media Catching: A Conceptual Framework for Understanding Strategic Mediatization in Public Relations?. Issue 2 (15th March 2018) - Erzikova, Elina; Waters, Richard; Bocharsky, Konstantin
ABSTRACT: A form of strategic mediatization, media catching is the reversal of the traditional public relations process of pitching story ideas to journalists using press releases, feature pitch letters, and other techniques. In media catching, journalists working on specific stories reach out to large numbers of public relations practitioners using a variety of technologically aided services with queries for specific information. Using quantitative and qualitative content analyses, this study examines journalist queries submitted through a media request service, Pressfeed.ru, to understand the dynamics of the media-catching trend in Russia. Findings show a substantial gap between reporters' expectations and public relations professionals' goals and abilities, and a fragmentation of media outlets' practices. The findings also revealed similarities in the growth and usage patterns of the Russian service to the first American media-catching service, Help-a-Reporter-Out. An empirical investigation is warranted to test an emergent model of the mutual influences of reporters, public relations specialists, internal (organizational values) and external (societal culture, political climate) factors during the process of media catching across different cultures and countries.